2003
DOI: 10.1097/00004650-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Caregiving and Care Receiving

Abstract: Spirituality is a part of holistic care for clients and families. This qualitative, descriptive study examined spirituality in 60 caregivers and 60 care receivers, equally divided between Caucasians and African Americans. Themes were coping (subthemes of formal religion and social support) and meaning (subthemes of positive attitude, retribution or reward, and all encompassing). Needs of caregivers and care receivers include opportunities for formal religion (communion, prayer), social support (visiting, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
3
16
1
Order By: Relevance
“…The review further suggests that these benefits may play a part in enhancing psychological health and encouraging physical well-being. A number of previous studies confirm the benefits of religious belief among carers -particularly relatives of individuals who live with dementia (Burgener, 1999;Paun, 2004;Theis, Biordi, Coeling, Nalepka, & Miller, 2003). The findings of these studies confirm the general suggestion that religious beliefs and practices provide a framework that helps carers to cultivate hope and acceptance, and identify some greater meaning in their situations.…”
Section: Supportsupporting
confidence: 68%
“…The review further suggests that these benefits may play a part in enhancing psychological health and encouraging physical well-being. A number of previous studies confirm the benefits of religious belief among carers -particularly relatives of individuals who live with dementia (Burgener, 1999;Paun, 2004;Theis, Biordi, Coeling, Nalepka, & Miller, 2003). The findings of these studies confirm the general suggestion that religious beliefs and practices provide a framework that helps carers to cultivate hope and acceptance, and identify some greater meaning in their situations.…”
Section: Supportsupporting
confidence: 68%
“…This study contributes much needed information about spirituality and caregivers of stroke survivors, which is an outcome of their participation in the e-mail discussion group. This is a distinction between this study and others reported (Jones-Cannon & Davis, 2005;Murray, 2004;Paun, 2004;Pierce, 2001;Sawatzky & Fowler-Kerry, 2003;Taylor, 2003Taylor, , 2006Theis et al, 2003), as messages were most often unsolicited and arose from the caregivers or in response to the nurse specialist facilitator and other caregivers, providing an indication of what was meaningful to them during the first year of caring. Spirituality, which gave caregivers of stroke survivors hope, sustenance, and a chance to express themselves more fully, enabled them to cope during a time of change.…”
contrasting
confidence: 62%
“…Compared with other people with serious illnesses, cancer patients have reported the highest percentage of religious coping responses [10]. Indeed, reporting a connection with a benevolent and loving God, religious involvement and spiritual practice have been associated with higher levels of hope [11,12], and ability to find meaning [13]. Although spirituality and/or religion can be an important resource to many people dealing with illness, sickness can also profoundly shake patients' most fundamental, religious or spiritual (R/S) beliefs and practices leading to R/S struggle or distress, also referred to as negative religious coping (NRC).…”
Section: Introductionmentioning
confidence: 99%